Soil loss from an oil palm plantation - Azizah, Mohd. Sabri. (Universiti Malaysia Sarawak (UNIMAS), 1998)
The Universal Soil Loss Equation (USLE) was applied to predict annual soil loss from an oil palm plantation. Parameters of the (ISLE used to generate the relevant raster layersfor soil erosion spatial modelling in the GIS are rainfall erosivity; • slope length/gradient; • cover-conservation method; • soil erodibility Using Geographical Information System (GIS) analysis and modelling technique, the fourfactors were used to generate the erosion risk map. Information contained in the map would allow planners to predict the average annual rates of the soil erosion with different landuse that are jungle, shifting cultivation, bare soil and oil palm. GIS is an effective tool in prediction ofthe soil loss.